Strength and capillary water absorption of lightweight concrete under different curing conditions - Bozkurt, Nusret; Yazicioglu, Salih (Natl Inst Science Communication-Niscair, 2010)
This paper reports an experimental study carried out to investigate the influence of addition of pozzolanic materials and curing regimes on the mechanical properties and the capillary water absorption (sorptivity) characteristics of lightweight concrete. A control lightweight concrete mixture made with lightweight volcanic pumice containing only Portland cement (PC) and fly ash lightweight concrete mixture containing 20% of fly ash (FA) and 10% of silica fume (SF) as a replacement of the cement by weight is prepared. The specimens are prepared and cured in three different curing conditions (standard 20 C water, sealed and air cured) for the periods of 3, 7 and 28 days. At the end of each curing period, compressive and tensile strengths and ultrasonic pulse velocity (UPV) values are determined; sorptivity coefficients are recorded at 28 days. The results indicate that SF specimens give higher compressive and tensile strength and lower sorptivity coefficient values than corresponding PC and FA concrete specimens, regardless of curing regime and age of concrete. The results also show a good correlation between the strength development of concrete and its sorptivity, i.e., as the compressive and tensile strengths increased due to the hydration, the sorptivity coefficients decreased significantly.
Keywords: Lightweight concrete; Curing regime; Mineral admixture; Sorptivity coefficient; Fly ash; Silica fume